India's economy - "Kapila, Raj (ed.)" (New Delhi, 2006)
From growth, poverty, and reform to globalization and sectorial developments, the 20 essays by leading economists address potential problems but coalesce to form an optimistic picture of India$1 (Bs future.s
Keywords: "India - Economic conditions, 1947"